Financial and investment instruments to strengthen the resilience of agricultural enterprises - Kalinichenko, Sergiy; Kryukova, Irina (Національний технічний університет "Харківський політехнічний інститут", 2025)
The study is aimed at systematizing modern approaches to managing financial flows in the agricultural sector, identifying opportunities for attracting investment resources and formulating recommendations for increasing the level of financial security of agricultural producers. It was determined that in conditions of economic turbulence, military challenges and instability of the market environment, it is the effective management of financial resources that is the key factor in ensuring the stability and competitiveness of agricultural enterprises. A generalization of modern financial instruments used in domestic and European practice was carried out, including lending, leasing, agricultural risk insurance, agricultural receipts, securities, investment funds and mechanisms of public-private partnership. It was established that the most promising instruments for Ukrainian agricultural enterprises are those that combine state support and private capital, in particular, preferential lending, EU grant programs, target investment funds for the development of agribusiness, as well as the "green" bond market, focused on financing environmentally responsible production.

Дослідження спрямоване на систематизацію сучасних підходів до управління фінансовими потоками в аграрному секторі, виявлення можливостей залучення інвестиційних ресурсів і формування рекомендацій щодо підвищення рівня фінансової безпеки сільськогосподарських виробників. Визначено, що в умовах економічної турбулентності, воєнних викликів та нестабільності ринкового середовища саме ефективне управління фінансовими ресурсами виступає ключовим чинником забезпечення стійкості та конкурентоспроможності аграрних підприємств. Проведено узагальнення сучасних фінансових інструментів, що застосовуються у вітчизняній та європейській практиці, серед яких — кредитування, лізинг, страхування агроризиків, аграрні розписки, цінні папери, інвестиційні фонди та механізми державно-приватного партнерства. Встановлено, що для українських аграрних підприємств найбільш перспективними є інструменти, які поєднують державну підтримку та приватний капітал, зокрема пільгове кредитування, грантові програми ЄС, цільові інвестиційні фонди розвитку агробізнесу, а також ринок «зелених» облігацій, орієнтований на фінансування екологічно відповідального виробництва.
Фінансово-інвестиційні інструменти зміцнення стійкості аграрних підприємств
Keywords: stability; instruments; investments; capital; risks; стійкість; інструменти; інвестиції; капітал; ризики